Twenty years ago: Hungarian Police Officers under the auspices of the UN in Cambodia (1992–1993) (Academic Journal of Internal Affairs, 2013)
The author describes the experiences of the largest UNTAC mission, involving 22,000 peacekeepers.
Keywords: UNTAC; Cambodia; United Nations